Women's empowerment for sustainability in Africa - Dibie, Robert A., 1956- (Newcastle upon Tyne : Cambridge Scholars Publishing, 2018)
This book uses an open, explorative approach to deal with the different aspects of gender discrimination and gender empowerment policies, as well as their impact on economic development and capacity-building in several African countries. It uses primary and secondary data to present the argument that, without the full input of women, sustainable development will not be achieved in many African countries. This book is the first text written by knowledgeable gender issue experts that understand the culture of, and lived and conducted research in, Africa. It provides many examples of the relation.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Women in development -- Economic aspects -- Africa; Women in development -- Government policy -- Africa; Sustainable development -- Africa; Mujeres en el desarrollo -- Aspectos económicos -- África.; Mujeres en el desarrollo -- Política gubernamental -- África.; Desarrollo sostenible -- África.; Libros electrónicos.